SISTEM INFORMASI PENJUALAN MOBIL BEKAS BERBASIS WEB PADA CV PHUTU OIL CLUB DI KOTA BATAM - Wahyudi, Muhammad Deni; Ridho, Muhammat Rasid (LPPM Universitas Putera Batam, 2019)
The website is an electronic page that can be accessed information whenever and wherever its location depends on the user's internet access from the system. By utilizing the web, many things can be created and developed in the world of buying and selling. Applicable sales, for example, are information systems for selling used cars in Batam. If the owner sells used cars already has a web-based information system, the seller and website manager will easily sell their products. The purpose of this information system is to help people find information on used car sales in Batam city through the internet using websites and other electronic media. web-based information system at CV Phutu Oil Club is a service that is intended for the community or users. The author developed a Web-Based Used Car Sales Information System at CV Phutu Oil Club in Batam City with the Waterfall method. The waterfall method is often also called a linear (sequential linear) model or classic life cycle. The waterfall model provides a sequential or sequential software lifeline approach starting from analysis, design, coding and testing.